THE MODERATING ROLE OF ESG DISCLOSURE ON FIRM STRATEGY AND STOCK PRICE CRASH RISK - Gregorius Jeandry; Nurdin (Universitas Airlangga, 2023)
This study aims to examine the effect of the company's business strategy on the stock price crash risk and examine the role of ESG disclosure as moderation in the relationship between business strategy and the stock price crash risk. The study population includes all companies listed on the Indonesia Stock Exchange (IDX) for the period 2017–2022. The sampling technique used was saturation sampling, with a total of 609 observations. Data collection techniques use content analysis. The data analysis technique uses ordinary least squares. This study found that firm strategy with the prospector typology affect the stock price crash risk, while the defenders and analyzers typologies have no effect on the stock price crash risk. ESG disclosure can weaken the effect of the business strategies of the prospector, defender, and analyzer typologies on stock price crash risk. Additional analysis found that ESG can reduce the risk of future stock price crashes. The contribution to signal theory is that there is consistently a strategic motivation for management to control good and bad information for the public. Bad information can cause the risk of price crashes to be higher than good information. Through ESG disclosure, it can provide positive signals to the public so that the risk of stock price crashes is low. The practical contribution for investors is as an investment strategy by paying more attention to the tendency of stock price crashes. For the government as a basis for making economic policies to create a well-maintained business climate.